A DNA Aptamer Targeting Cellular Fibronectin Rather Than Plasma Fibronectin for Bioimaging and Targeted Chemotherapy of Tumors. (10th August 2022) - Zou, Yujian; Wang, Yufei; Wen, Xiaohong; Li, Chihao; Lei, Lei; Guo, Qiuping; Sun, Guoming; Yu, Li; Nie, Hemin
Abstract: Fibronectin (FN) is a well‐established hallmark of epithelial‐to‐mesenchymal transition, and may serve as an omnipresent cancer biomarker regardless of the origins of tumor cells. An ssDNA aptamer (ZY‐1) with highly selective binding affinity to mesenchymal stromal cells is previously developed, but the binding target of ZY‐1 on the cells and the underlying mechanism is yet to be understood. Here, the identification of FN as the target protein of aptamer ZY‐1 is reported for the first time and the mechanism of ZY‐1 binding to cFN is explored. The data indicate that ZY‐1 solely recognizes cellular fibronectin (cFN) rather than plasma fibronectin (pFN). The ZY‐1 binding to cFN is explored through computational modeling and the competition of heparin in binding cFN owing to steric hindrance is confirmed. The in vitro assay and noninvasive in vivo fluorescence imaging results validate the specificity of ZY‐1 in targeting cFN and sensitivity in detecting tumors. The ZY‐1‐mediated targeted cancer therapy using a proof‐of‐concept study with a ZY‐1‐based complex loaded with doxorubicin (Dox) is further proved. This study would facilitate more comprehensive studies of anti‐FN aptamers in the imaging and treatment of tumors and other FN‐associated diseases. Abstract : A DNA aptamer ZY‐1 targeting cellular fibronectin (cFN) rather than plasma fibronectin (pFN) is developed and the underlying mechanism of ZY‐1 in distinguishing between cFN and pFN is comprehensively elaborated. The enhanced binding of ZY‐1 to over‐accumulated cFN in tumors enables bioimaging and FN‐targeted chemotherapy of tumors.